Long-Term Demographic and Spatio-Temporal Trends of Indo-Pacific Bottlenose Dolphin (Tursiops aduncus) Bycatch in Bather Protection Nets off KwaZulu-Natal, South Africa - Plön, Stephanie; Erbe, Christine; Wintner, Sabine (Frontiers in Marine Science, 2020)
Bather protection nets have been in place off the coast of KwaZulu-Natal (KZN), South Africa, since the 1950’s. Besides sharks, they also catch a number of other marine vertebrates, including dolphins, the majority of which are Indo-Pacific bottlenose dolphins Tursiops aduncus. Previous analyses of dolphin bycatch in the nets expressed concern about the potential impacts on the local populations, but a lack of information on population structure has to-date hindered a more detailed assessment. A recent re-assessment of the status and population delineations of T. aduncus off South Africa prompted a re-examination of demographic, spatial, and temporal patterns of its catches in bather protection nets over a 36-year period (January 1980 to December 2015). In total, 1169 dolphins were caught and the different sexes and age groups are impacted to different degrees, raising concern about the potential long-term effects on population demographics. North Coast and South Coast populations face different impacts from bycatch in the nets. Temporal trends indicate that the bycatch during June and July every year (peak Sardine Run period) as a percentage of overall dolphin bycatch has been steadily decreasing from 39.8% in 1980 to 13% in 2015. A large inter-annual fluctuation can be seen, probably as a result of the inter-annual intensity of the Sardine Run. To accurately assess the impact of bycatch on the Indo-Pacific bottlenose dolphin populations off KZN, revised abundance estimates and data on the demographics and movement patterns of the individual populations are urgently required for conservation and management decisions going forward.